2022
DOI: 10.1093/emph/eoac027
|View full text |Cite
|
Sign up to set email alerts
|

Child dietary patterns in Homo sapiens evolution

Abstract: Dietary patterns spanning millennia could inform contemporary public health nutrition. Children are largely absent from evidence describing diets throughout human evolution, despite prevalent malnutrition today signaling a potential genome-environment divergence. This systematic review aimed to identify dietary patterns of children ages 6 months to 10 years consumed before the widespread adoption of agriculture. Metrics of mention frequency (counts of food types reported) and food groups (globally standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Livestock ownership was negatively associated with any ASF consumption suggesting the use of livestock for other purposes besides household food consumption, for example, as draft animals or for income generation. On a global scale, aquatic ASF contributes high proportions of docosahexaenoic acid, choline, and vitamin B12 nutrition, and crustaceans more specifically are associated with reduced stunting [ 56 ]. Small fish are often more accessible to low-resource populations and provide high concentrations of critical micronutrients comparable with fortified food supplements [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Livestock ownership was negatively associated with any ASF consumption suggesting the use of livestock for other purposes besides household food consumption, for example, as draft animals or for income generation. On a global scale, aquatic ASF contributes high proportions of docosahexaenoic acid, choline, and vitamin B12 nutrition, and crustaceans more specifically are associated with reduced stunting [ 56 ]. Small fish are often more accessible to low-resource populations and provide high concentrations of critical micronutrients comparable with fortified food supplements [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain animal species cannot correctly utilize xylitol, especially carnivores that have not been evolutionarily exposed to plants as foods 41. Tubers were once a significant source of food for homo sapiens and still a survivor food for hunter-gatherers, such as the Hadza tribe [42,43]. The microbiome of hunter-gatherers and traditional tribal people maintains specific bacterial taxa that can utilize complex carbohydrates and polyols [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence generally associating UPF consumption with reduced intake of several critical nutrients, some representative epidemiological studies have specifically observed increased intake of Calcium in relation to increased UPF intake ( 34 , 72 , 73 ) . It is however important to recognise that dietary patterns and nutrient interactions within a diet matrix – rather than a single nutrient – are better predictors for nutrition-related outcomes ( 74 , 75 ) . Emerging experimental evidence mostly points to the negative impacts of increased UPF intake on bone health.…”
Section: Discussionmentioning
confidence: 99%